PENGARUH PARENTING TERHADAP PRESTASI BELAJAR MATEMATIKA PESERTA DIDIK - Mohammad Ardani Samad; Mangindara Mangindara (STKIP Andi Matappa, 2020)
This research is Ex-post Facto research with quantitative approach and comparative causal research design. This study aims to find out whether or not the influence of parenting on the achievements of mathematics learning Grade VII SMP Negeri in Sungguminasa. The population used in this study was students of grade VII smp negeri in Sungguminasa. The sample in this study was 64 students who were in smp negeri 4 Sungguminasa school. Sampling using random sampling techniques. Data collection using questionnaire methods and documentation. Before the data analysis is conducted first test the analysis requirements that include normality test, homogeneity test. The data analysis technique used to test hypotheses is Variant Analysis (ANOVA) with one-way Anova type. The results showed that there is an influence of parenting on the achievement of mathematics learning grade VII smp negeri in Sungguminasa. This is indicated by the Fcalculate value (31,375) > Ftabel (3.32) and the Sig value of 0.000 < 0.05 which means there is a meaningful difference on average in all parenting groups.